SISTEM PENGENDALI INTENSITAS CAHAYA PADA LAMPU PENERANGAN RUANGAN BERDASARKAN SENSOR CAHAYA PADA SMARTPHONE ANDROID - , HANIFAN MUSHTHAFA, Triyogatama Wahyu Widodo, S.Kom., M.Kom. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Lighting a room with excessive light intensity can certainly dazzle, otherwise low light intensity can make the object in the room can not be seen clearly, fluctuate condition of light intensity also can interfere the activity in the room. The room condition can follow the changing outdor condition, for example during overcast condition in the daylight, at the time of sunrise or sunset. Light intensity can be changed at any time, not accordance with the vision needs, so that can be interfere with the activity in the room. Therefore mechanism to set the light intensity of the lamp that would be able to control the light that dynamically depends on the light intensity and need of user. In order to adjust the lamp intensity in a room, this research use the light sensor in the Android smartphone with interface application that connect with switch controller. Switch and Android smartphone work integratively by using WiFi connection.The design of mechanism or protocol of data communication between switch and user application is needed to work effectively. The result of system implementation is then being tested on a several test. To test the function of WiFi connection, comparing between Android smartphone light sensor vs luxmeter test, lamp dimmer test, protocol test, and control system test. The result of research show that the value of android smartphone light sensor used in research not accurate to used to the mechanism because it does not correspond to the actual light intensity value based on Luxmeter Lx-100. In mechanism with setpoint based on Android smartphone light sensor readings at 403 Lux gained 1.6 seconds rise time, 2.2 seconds peak time, overshoot 59%, 2.4 seconds settling time. Keywords : light sensor, Android smartphone, WiFi, light intensity control